Context Matters: A Critique of Agency Theory in Corporate Governance Research in Emerging Countries - Yusof, Nor Zalina Mohamad (International Journal of Economics and Financial Issues, 2016)
This paper aims to provide an overview of the trend or focus in the research of corporate governance in emerging countries with the aim to identify the gaps in the existing literature. The review notes that corporate governance research in emerging countries is dominated by economic perspective, in particular the agency theory, as researchers follow the strands of research conducted in the more advanced countries, especially the US and the UK. This paper argues that although influential, agency theory is unable to provide sufficient understanding on many issues related to practices for the fact that corporate governance is not happening in social vacuum; it is affected by various other institutional factors and local context. Hence, in order to gain better understanding of corporate governance in emerging countries, alternatives perspectives or theories, such as institutional theory, should be employed by the researchers. Keywords: Corporate Governance; Developing Economies; Agency Theory; Institution JEL Classification: M41